Wege und Ziele der chemischen Forschung an der Hochschule: Erfahrungen auf dem Gebiete der Farbstoff- und Textilchemie - H. Zollinger (CHIMIA)
The experience gained in research in dyestuff and textile chemistry is used as a basis to discuss the problems and potential goals of academic research at the present time. In addition to receiving training in specific scientific methods in a particular area of research, it is important that graduate students are well acquainted with the basic principles of general science, with research planning and with the problem of information exchange. Some specific research problems treated at the Department of Industrial and Engineering Chemistry, ETH Zurich, are summarized briefly.